2008
DOI: 10.1243/14644193jmbd154
|View full text |Cite
|
Sign up to set email alerts
|

Large-scale parallel multi-body dynamics with frictional contact on the graphical processing unit

Abstract: In the context of simulating the frictional contact dynamics of large systems of rigid bodies, this paper reviews a novel method for solving large cone complementarity problems by means of a fixed-point iteration algorithm. The method is an extension of the Gauss-Seidel and Gauss-Jacobi methods with over-relaxation for symmetric convex linear complementarity problems. Convergent under fairly standard assumptions, the method is implemented in a parallel framework by using a single instruction multiple data comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
55
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(55 citation statements)
references
References 32 publications
0
55
0
Order By: Relevance
“…Another drawback of the regularized approach is that the difficulty to chosen the contact parameters such as the equivalent stiffness or the degree of nonlinearity of the deformation, especially for complex contact scenarios [33]. An alternative way to treat the contact-impact problems in multibody systems is to use the non-smooth dynamics approach, namely the Linear Complementary Problem (LCP) [34,35] and Differential Variational Inequality (DVI) [36,37]. The complementarity formulations associated with the Moreau's time-stepping algorithm for contact modeling in multibody systems have used by many researchers [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another drawback of the regularized approach is that the difficulty to chosen the contact parameters such as the equivalent stiffness or the degree of nonlinearity of the deformation, especially for complex contact scenarios [33]. An alternative way to treat the contact-impact problems in multibody systems is to use the non-smooth dynamics approach, namely the Linear Complementary Problem (LCP) [34,35] and Differential Variational Inequality (DVI) [36,37]. The complementarity formulations associated with the Moreau's time-stepping algorithm for contact modeling in multibody systems have used by many researchers [38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…However, the algorithmic procedures that results from DVI approach is of great complexity. This formalism has been used with success by Tasora et al [37] to model and analyze multibody systems involving hundreds of thousand contacts. The DVI approaches are also interesting in the measure that they can easily deal with friction problems without need to modify Coulomb's friction law.…”
Section: Introductionmentioning
confidence: 99%
“…The method has been recently ported also on parallel stream-kernel GPU hardware, obtaining a remarkable computational efficiency [44].…”
Section: Discussionmentioning
confidence: 99%
“…Previous sections showed that generic multibody problems with frictional contacts, expressed with the system (15)- (19), embed the cone complementarity problem (42), which can be solved by the iterative method (44).…”
Section: Methodsmentioning
confidence: 99%
“…Since separation or gap between material points in an ensemble has traditionally been used to describe the various action potentials, the mechanism of contact is often used to trigger simple interactions for a large number of material points. Newton-Euler method lends itself well to representation of such systems, thus as presented in references [14], [27], and [28] M q dq dt = F q,q + f q (13) where M q is the inertial matrix, F q,q is the vector of generalized forces such as coriolis, centripedal, and generalized smooth contact forces (e.g. viscous and Stribeck effects), and f q is the sum of friction components of generalized contact forces.…”
Section: Many-body Systemsmentioning
confidence: 99%